Social well-being of youth: searching for problem areas (The Journal of Psychology and Sociology, 2015)
The current economic situation in the world and the country has a direct impact on the social wellbeing and mood of society, including the youth. As we know, the youth is characterized by a high degree of sensitivity and in the current situation, it is important assessment of emotional disposition of the young generation. Most of the young people enter into an independent life in conditions of institutional changes of spheres of economy, education and culture. These were decisive prerequisites for changes of living space of young people. In this situation, namely the extreme sensitivity and high social mobility of characteristics of young people and the mentality in valuenormative sense began to change. The article presents some data on a comprehensive assess ment of social wellbeing and mood of the younger generation, as well as the degree of satisfaction by quality of life indicators, the most important of them: such as financial status, living conditions, health, circle of contacts (friends and acquaintances), education, relations in the collective / in the group, earning op portunities, getting a wellpaid job, opportunities of opening business. Given the current economic situation in the world, it can be assumed that the country’s youth feel less satisfied with their lives than previous generations. Our research shows that this option includes a variety of factors, including the level of subjec tive wellbeing, the evaluation of material status and satisfaction with them, life strategies and prospects for the future. Thus satisfaction factors need to be evalu ated in such a way they can cover all aspects of life. In the research, the largest share of respondents composed student youth: they are students (25.9%) and pupils (10.1%). The percentage of unemployed persons of various categories, this means registered at the labor exchange or not is 5.6% of the total number of respondents. Number of respondents registered at the labor exchange about 2%. Among respondents 11.3% engaged in public service, 22.5% work in the field of private entrepreneurship, in a private firm or company, including its own business (selfemployment). This article was prepared within the research project at IFPR of MES “worldview and spiritual values of youth in Kazakhstan at the present stage: assessment of the status, problems and solutions”. The main searching of the scientific project during three years was aimed at identifying features of potential changes taking place in society and their reflection in the value consciousness of the younger generation.
Keywords: social wellbeing of youth; youth`s expectations; satisfaction with lives.